Gene flow from herbicide resistant transgenic soybean to conventional soybean and wild soybean - Kim, Hye Jin; Kim, Do Young; Moon, Ye Seul; Pack, In Soon; Park, Kee Woong; Chung, Young Soo; Kim, Young Joong; Nam, Kyong-Hee; Kim, Chang-Gi (Applied biological chemistry, 2019)
Gene flow from transgenic crops to conventional cultivars or wild relatives is a major environmental and economic concern in many countries. South Korea is one of the major importer of transgenic crops for food and feed, although commercial cultivation of transgenic crops is not yet allowed in this country. This study evaluated gene flow from the herbicide glyphosate- and glufosinate-resistant transgenic soybean ( Glycine max ) to five non-transgenic soybean cultivars and three accessions of wild soybean ( Glycine soja ). Field trials were conducted over 2 years, and gene flow was monitored up to 10 m distance from the pollen source. The results indicated that the detectable rate of gene flow from transgenic to conventional soybeans varied between 0 and 0.049% in both 2014 and 2015 field trials, while no hybrids were detected among wild soybean progenies. The highest rate of gene flow was found in the progenies of the Bert cultivar, which exhibited the longest period of flowering synchronization between the pollen donor and the recipient. In addition, overall gene flow rates declined with increased distance from the transgenic soybean plot. Gene flow was observed up to 3 m and 8 m from the transgenic soybean plot in 2014 and 2015, respectively. Our results may be useful for developing measures to prevent gene flow from transgenic soybean.